Source Apportionment, transport and fate of pollutants in the paper recycling chain - An analytical exploration of the South African context - Mofokeng, Nondumiso Nomonde Radebe (University of the Witwatersrand, Johannesburg, 2024)
This thesis presents the analytical exploration of pollutants in the South African paper recycling chain. Recycled paper is a valuable commodity that forms an intrinsic part of actualising a circular economy. In South Africa, the recycled paper value chain includes largely unsorted waste paper recovered from household waste, businesses, retail, schools, industry as well as paper collected from public areas, solid waste disposal sites and landfills by informal waste pickers. Extensive research has been undertaken in Europe, America, and Asia on the implications of using recycled paper; specifically, in packaging intended for food, toys, and electric equipment. In South Africa, however, research on pollutants in recycled paper does not exist. As the global impetus towards sustainability increases, it is imperative to determine the type of pollutants that may arise from the recycled paper value chain as these may negatively affect humans and the surrounding biota. This study extended beyond typical food packaging migration studies and investigated the holistic extraction of both food and non-food paper-based materials. The stages of paper recycling that were investigated were pre-consumer, retail and post-consumer. In Paper 1, liquid and gas chromatography, both in tandem with mass-spectrometry, were used for the chemical characterisation of various paper recycling grades prepared by accelerated solvent extraction and ultrasonic assisted extraction, respectively. The findings indicated that polymer-associated chemicals such as plasticizers, antioxidants, flame retardants, and polymer degradants have infiltrated the paper recycling chain. Multi-residue quantification of 11 pollutants in recycling paper grades in South Africa using GC-MS after accelerated solvent extraction was the main focus of Paper 2. The target analytes included BBP, DEP, DBP, DEHP, DIBP, DIDP, DIPN, NBBS, BHT, AO168, and AO168O. A plot of the VIPscores showed that DEHP and DBP were the most prominent pollutants, whilst AO168 and BHT were the least significant pollutants in the examined samples. Paper 3 explored the previously unexplored contamination of paper by pharmaceuticals, emerging contaminants that have been historically detected in South African environmental matrices. The analyses were achieved by ultrasonic-assisted extraction of paper samples before targeted and suspect screening by UHPLC-Q Orbitrap. This study was able to uncover the presence of dexamethasone, ketoprofen, and 17β-estradiol in paper-based samples. In addition, suspect screening was able to tentatively identify additional pharmaceuticals through spectral database matches. Papers 4 and 5 studied PFAS prevalence in recycling paper grades used for the manufacture of recycled paperboard. In Paper 4, targeted analysis of per- and polyfluoralkyl carboxylic and sulphonic acids was undertaken. The possible propagation and amplification of PFAS was explored by comparing the concentrations detected in pre-consumer samples to those detected in retail and post-consumer samples. Suspect screening in Paper 5 tentatively identified additional PFAS present in the samples through the development of a study-specific suspect screening protocol reported with its associated confidence level. The samples were prepared using two extraction techniques; accelerated solvent extraction with solid-phase extraction and ultrasonic-assisted extraction. The different functional groups identified indicated the importance of both selective and non-selective extraction in understanding PFAS occurrence. It further demonstrated an urgent global need to understand the different PFAS that can occur in the paper recycling chain. In these Papers, manufacturing additives and retail activities were identified as possible exposure sources. Post-consumer usage, collection, sorting, and comingling of various waste materials were also identified factors that influence the prevalence of pollutants. The presence of certain pollutants in pre-consumer showed that certain compounds may potentially remain within the paper recycling chain, propagate and accumulate along with those from the retail and postconsumer stages. The lower abundance in comparison to retail and post-consumer samples indicated that other pollutants may likely be removed during the reprocessing of recycled fibre. This study thus showed that it is imperative that South Africa develop and implement legislation and guidelines that address the use, risk, and standardised waste management strategies that ensure a safe circular economy in the paper recycling chain.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024
Keywords: Recycled paperboard; Emerging contaminants; Chromatography; Mass spectrometry; Environmental analytical chemistry; UCTD; SDG-13: Climate action; SDG-11: Sustainable cities and communities